Correlation between Long-Term Exposure to Traffic Noise and Risk of Type 2 Diabetes Mellitus - Zhaopeng Yu; Maomin Song (Noise and Health)
Objective: This study aimed to probe the correlation of long-term exposure to traffic noise with the risk of type 2 diabetes mellitus (T2DM). Methods: The data of 480 community residents collected from April 2017 to April 2018 were retrospectively analyzed. Exposure levels for traffic noise were defined using 24-h mean traffic noise. Logistic regression calculated the association between long-term exposure to traffic noise and the risk of T2DM. Results: Overall, 480 enrolled participants were divided into T2DM (n = 45) and non-T2DM (n = 435) groups. Participants with T2DM were older and more likely to be male, had higher BMI, and were frequent drinkers (P < 0.001). The T2DM group displayed higher exposure to traffic noise than the non-T2DM group (P < 0.001). According to quartiles of traffic noise, all participants were categorized into four groups: Q1 (<51.5 dB), Q2 (51.5–<53.9 dB), Q3 (53.9–<58.0 dB), and Q4 (≥58.0 dB). Prevalence of T2DM was 5.4% in Q1, 7.7% in Q2, 10.3% in Q3, and 14.1% in Q4 groups. Multifactor regression analysis showed that age, BMI, drinking history, and traffic noise exposure are risk factors for T2DM (P < 0.05), whereas sex does not seem to have a significant impact on T2DM (P > 0.05). Conclusion: Long-term exposure to traffic noise may elevate the risk of T2DM. This suggests that long-term exposure to high levels of traffic noise can increase the incidence of diabetes mellitus, which deserves further consideration.